2017
DOI: 10.1002/path.4911
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase (FAK) tyrosine 397E mutation restores the vascular leakage defect in endothelium‐specific FAK‐kinase dead mice

Abstract: Focal adhesion kinase (FAK) inhibitors have been developed as potential anticancer agents and are undergoing clinical trials. In vitro activation of the FAK kinase domain triggers autophosphorylation of Y397, Src activation, and subsequent phosphorylation of other FAK tyrosine residues. However, how FAK Y397 mutations affect FAK kinase‐dead (KD) phenotypes in tumour angiogenesis in vivo is unknown. We developed three Pdgfb‐iCreert‐driven endothelial cell (EC)‐specific, tamoxifen‐inducible homozygous mutant mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 48 publications
4
28
0
Order By: Relevance
“…We next sought to investigate how FAK-Y397F and FAK-Y861F mutations differentially affect downstream signaling and compare these responses with our previously published FAK-kinase dead (FAK-KD) mutant ECs (32). Western blot analysis of FAK-Y397F and FAK-KD ECs showed reduced FAK phosphorylation at Y397, Y577, Y861, and Y925.…”
Section: Nonphosphorylatable Mutations In Fak-y397 and Fak-y861 Residmentioning
confidence: 99%
“…We next sought to investigate how FAK-Y397F and FAK-Y861F mutations differentially affect downstream signaling and compare these responses with our previously published FAK-kinase dead (FAK-KD) mutant ECs (32). Western blot analysis of FAK-Y397F and FAK-KD ECs showed reduced FAK phosphorylation at Y397, Y577, Y861, and Y925.…”
Section: Nonphosphorylatable Mutations In Fak-y397 and Fak-y861 Residmentioning
confidence: 99%
“…Furthermore, FAK is essential for maintaining vascular functions in tumor angiogenesis. Lees et al [16] found that FAK recovered the vascular leakage defect through the activation of kinase domain. And it is a fact that cytokines induce vascular growth factor expression by the FAK signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…FAK is a 125 kDa non‐receptor protein tyrosine kinase which is located at sites of integrin clustering in focal adhesions; therefore, FAK plays a central role in cellular processes that include migration and adhesion . FAK has many phosphorylated tyrosine sites, and these sites are key for the signal transduction function of FAK.…”
Section: Introductionmentioning
confidence: 99%